Rola nasion szałwii hiszpańskiej (chia) w żywieniu pacjentów geriatrycznych = The role of chia seeds in nutrition in geriatric patients - Nowak, Karina; Majsterek, Szymon; Ciesielska, Natalia; Sokołowski, Remigiusz; Klimkiewicz, Karolina; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Nowak Karina, Majsterek Szymon, Ciesielska Natalia, Sokołowski Remigiusz, Klimkiewicz Karolina, Zukow Walery. Rola nasion szałwii hiszpańskiej (chia) w żywieniu pacjentów geriatrycznych = The role of chia seeds in nutrition in geriatric patients. Journal of Education, Health and Sport. 2016;6(3):35-40. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47416 http://ojs.ukw.edu.pl/index.php/johs/article/view/3419 https://pbn.nauka.gov.pl/works/719606 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Rola nasion szałwii hiszpańskiej (chia) w żywieniu pacjentów geriatrycznych The role of chia seeds in nutrition in geriatric patients Karina Nowak1, Szymon Majsterek3, Natalia Ciesielska1, Remigiusz Sokołowski2, Karolina Klimkiewicz1, Walery Zukow4 1Department and Clinic of Geriatrics, Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 2Department of Hygiene, Epidemiology and Ergonomic Division of Ergonomics and Exercise Physiology Nicolaus Copernicus University Collegium Medicum, Bydgoszcz, Poland 3Nicolaus Copernicus University, Toruń, Poland 4Kazimierz Wielki University, Bydgoszcz, Poland Słowa kluczowe: nasiona chia, szałwia hiszpańska, choroby sercowo-naczyniowe, zapobieganie, kwasy tłuszczowe omega-3, kwasy tłuszczowe omega-6. Key words: chia seeds , salvia hispanica , cardiovascular disease , prevention, omega-3 , omega-6. Streszczenie Pacjenci geriatryczni są specyficzną grupą chorych ze względu na to, iż w organizmie starszych osób dochodzi do wielu zmian związanych ze starzeniem się organizmu. Pogarsza się wydolność wielu układów m.in. układu pokarmowego, oddechowego oraz pojawiają się zmiany w naczyniach. Zmiany w motoryce przełyku zwane przełykiem starczym są skutkiem chorób występujących w tej grupie wiekowej. Zmniejsza się kwasowość soku żołądkowego co jest przyczyną zmian atroficznych w błonie śluzowej oraz nadużycia inhibitorów pompy protonowej. Dochodzi również do obniżenia liczby hepatocytów a tym samym zmniejszenia masy wątroby. Do zmian w układzie moczowym zaliczamy zmniejszoną zdolność do zagęszczania i rozcieńczenia moczu a także regulacji pH [1]. Osoby starsze często chorują na nadciśnienie, miażdżycę czy inne schorzenia sercowo-naczyniowe. Do produktów, będących źródłem wielu witamin, minerałów czy składników pożądanych w diecie seniorów możemy zaliczyć nasiona chia. Małe ziarenka, bogate w białko oraz kwasy tłuszczowe omega-3 i omega-6, zawierające w 100g więcej wapnia niż mleko mogą stać się ważnym elementem w diecie osób starszych. Zawarty w nich kwas alfa-linolenowy (ALA) może obniżać ciśnienie tętnicze krwi u osób z nieleczonym nadciśnieniem, wspomaga pracę mózgu, poprawia pamięć i koncentrację oraz posiada działanie protekcyjne na układ krążenia. Badanie GISSI-Prevention Study wykazało, że kwasy omega-3 mogą zmniejszać ryzyko nagłego zgonu, umieralności całkowitej oraz sercowo-naczyniowej u chorych po świeżo przebytym zawale mięśnia sercowego [2]. Abstract Geriatric patients are a special group of patients, due to the fact that the body of older people there are many changes associated with aging of the body. Deteriorating performance of many systems including the gastrointestinal tract, and respiratory changes occur in the vessels. Changes in the motility of the esophagus called esophageal senile are the result of diseases that occur in this age group. This reduces the acidity of the gastric juice which is the cause of atrophic mucosa and misuse of proton pump inhibitors. This leads also to a reduction in the number of hepatocytes and thereby reduce the weight of the liver. Changes in the urinary system include reduced ability to concentrate and dilute urine and pH adjustment [1]. Older people often suffer from hypertension, atherosclerosis and other cardiovascular diseases. Products, which are the source of many vitamins, minerals or desirable ingredients in the diet of seniors can include chia seeds. Small grains, rich in protein and fatty acids omega-3 and omega-6, containing 100g more calcium than milk can become an important element in the diet of older people. Included in these alpha-linolenic acid (ALA) may lower blood pressure in people with untreated hypertension, supports the work of the brain, improves memory and concentration and has protective effects on the cardiovascular system. GISSI-Prevention Study showed that omega-3 may reduce the risk of sudden death, total mortality and cardiovascular disease in patients after recent myocardial infarction [2]